PERUBAHAN DIVIDEN TUNAI SEBAGAI DAMPAK PERUBAHAN DARI LABA BERSIH, ARUS KAS OPERASI, DAN HARGA SAHAM - Vemy Suci Asih (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: The background of this research is the hope of investors to acquire large cash dividends from its investment in the Islamic capital market. In theory, the amount of cash dividends distributed by companies affected by corporate earnings net income and operating cash flows of the company. However in practice, when an increase in net income and the availability of cash flows from operating activities of the company, cash dividends are not always rise or even decline. In addition, cash dividends is affected by stock prices, the higher the stock price, the higher the dividend that can be distributed by the company. The method used is the method of analysis of secondary data on net income, operating cash flow, stock price and cash dividends were published on the official website of agencies and related institutions. Based on the test results with the partial t-test, the effect of net income to cash dividend has a significance value of 0.000 so it can be concluded that the significant effect on the net income of cash dividends. Effect of operating cash flow to cash dividend has a significance value of 0.557 so it can be concluded that operating cash flow is not a significant effect on cash dividends. The influence of stock price to cash dividend has a significance value of 0.004 so it can be concluded that stock prices have a significant effect on cash dividends. Based on the results of F-test net income, operating cash flow and stock price are jointly significant effect on cash dividends on listed companies in the Jakarta Islamic Index. Keywords: Cash Dividend, Net Income, Operating Cash Flow, Stock Prices